2015
DOI: 10.1152/ajpcell.00225.2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mechanisms of cancer cell migration through 3D matrix and physiological microtracks

Abstract: Tumor cell invasion through the stromal extracellular matrix (ECM) is a key feature of cancer metastasis, and understanding the cellular mechanisms of invasive migration is critical to the development of effective diagnostic and therapeutic strategies. Since cancer cell migration is highly adaptable to physiochemical properties of the ECM, it is critical to define these migration mechanisms in a context-specific manner. Although extensive work has characterized cancer cell migration in two- and three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
118
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 72 publications
2
118
1
1
Order By: Relevance
“…26,27 Mice were maintained according to Cornell University Animal Care guidelines, and methods were approved by the Cornell Institutional Animal Care and Use Committee (protocol 2009-0101; R.M. Williams).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Mice were maintained according to Cornell University Animal Care guidelines, and methods were approved by the Cornell Institutional Animal Care and Use Committee (protocol 2009-0101; R.M. Williams).…”
Section: Methodsmentioning
confidence: 99%
“…26 Briefly, collagen stock solution was diluted using ice-cold culture medium and neutralized with sodium hydroxide. Cells were incorporated into neutralized collagen and matrices were polymerized at room temperature for 30 min, at which point collagen matrices were fully polymerized as determined by stable matrix structure in time-lapse confocal reflectance images acquired as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the dependence of pseudopod elongation on microtubules was also observed in cancer cells that display a mesenchymal morphology in 3D, such as MDA-MB-231 cells ( Kikuchi and Takahashi, 2008;Oyanagi et al, 2012). High doses of paclitaxel or nocodazole blocked migration of these cells in soft collagen gels (Carey et al, 2015). In fact, even low doses of different microtubule-targeting agents (MTAs), which were insufficient to block cell division, impaired matrix invasion by MDA-MB-231 cells (Tran et al, 2009).…”
Section: Microtubule Requirement In Cell Morphogenesis and Motility Imentioning
confidence: 99%
“…In studying the influence of actomyosin contractility in migration through microtracks, Carey et al (1) found that pharmacological inhibition of Rho, Rho-associated protein kinase, or myosin light chain kinase reduced traction force but had no effect on the motile fraction or cell speed, indicating that traction forces are not required for microtrack migration. However, when myosin ATPase activity was inhibited directly, microtrack migration speed was significantly reduced, suggesting that a minimal level of myosin-mediated contractility is required for microtrack migration, likely by facilitating retraction of the lagging end.…”
mentioning
confidence: 99%
“…By comparing migration through 3D matrix with movement through microtracks, Carey et al (1) have revealed the adhesion and actinmyosin contraction requirements for cell migration along preexisting or cell-derived paths and have identified cell interactions with the ECM via ␤ 1 -integrin as an important modifier of invasive cell morphology, which enables tumor cells to use different migration mechanisms in response to varying microenvironmental contexts. Increased understanding of invasive cell migration, in terms of differences between leader and follower cells and in different external contexts, is necessary to identify new therapeutic targets and to realistically evaluate their clinical potential.…”
mentioning
confidence: 99%